The Nurse’s Role for Apply Self-Efficacy Theory in the Elderly Diabetic - จำปาเทศ นพนัฐ; แจ่มจันทร์ ละเอียด; ฝ่ายหมื่นไวย์ พัชราภรณ์ (Journal of Health Sciences and Wellness, 2018)
Diabetes is a chronic disease that is becoming more common, especially among the elderly. In addition to genetic factors, increasing age was a significant factor in the incidence of diabetes. Development of diabetes among elderly is common, as it is in any other age group, but it has unique characteristics that require specific care for the elderly, to delayed diagnosis or misdiagnosis due to the lack of classic symptoms, and due to complications that can be fatal care management is different from other age groups with the goal of preserving. The goal of care for elderly patients is to bring a better quality of life with focus on behavioral modification and prevention of complications. The application of selfefficacy theory in managing the health care of the elderly with diabetes aims to encourage older people with diabetes to know that they have the ability to choose the activities or behavior, that may affect their health outcomes, such as maintaining blood sugar levels effectively and preventing complications.